Bioweathering of Egyptian Nubian sandstone and Theban limestone: three months insight by experimental incubation - Potysz Anna; Osman Amr; Bartz Wojciech (Mineralogia)
This study undertook laboratory incubation approach to examine abiotic and biotic factors potentially influencing the bioweathering of Egyptian dimension stones, namely Nubian sandstone and Theban limestone. The dynamic and efficiency of metal release were assessed by means of bioleaching experiments (quantification by inductively coupled plasma mass spectrometry), whereas potential element donor phases were identified by scanning electron microscopy (SEM-EDS). Overall, biotic weathering plays more of an important role for initiation of limestone dissolution, whereas its contribution to sandstone dissolution is more specific to host minerals accommodating individual elements. Kaolinite and Fe-bearing cement minerals (ilmenite and magnetite) in sandstones were found to be particularly attractive to bacteria that enhanced Al and Fe leaching by factors up to 7.0 and 5.7, respectively. Leaching of Al and Fe from limestone was enhanced by a factor up to 13 in the presence of bacteria. Siderophore concentration in biotic incubation reached 45.2-75.5 μmol L−1 and 90.6 μmol L−1 for sandstones and limestone, respectively. Regardless of immersed solid, higher Ca and Mg leaching from calcite and dolomite under chemical instead of biotic conditions was observed indicating either preferential mineral colonization by bacteria or surface passivation by biofilm. At the end of chemical incubation, up to 34.1% of Ca and up to 27.0% of Mg were leached from sandstones, whereas leaching observed for limestone was up to 0.6% (Ca) and 16.3% (Mg). Limestone dissolution was assessed at up to 1.2% (Si). This study has implications for understanding the dissolution of dimension stone used as construction and building materials and cultural heritage objects such as monuments and ornaments.